Logistics flexibility and sustainability performance: the mediating role of supply chain resilience - GATI WISDOM (KNUST, 2024)
A thesis submitted to the department of supply chain and information systems, in partial fulfilment of the requirements of the award of the degree of master of science in logistics and supply chain management